Status of autophagy, lysosome activity and apoptosis during corpus luteum regression in cattle - ABOELENAIN, Mansour (J Reprod Dev, 2015)
Corpus luteum (CL) regression is required during the estrous cycle. During CL regression, luteal cells stop producing progesterone and are degraded by apoptosis. However, the detailed mechanism of CL regression in cattle has not been fully elucidated. The aim of this study was to evaluate autophagy, lysosome activity, and apoptosis during CL regression in cattle. The expression of autophagy-related genes (LC3α, LC3β, Atg3, and Atg7) and the protein LC3-II was significantly higher in the late CL than in the mid CL. In addition, autophagy activity was significantly increased in the late CL. Moreover, gene expression of the autophagy inhibitor mammalian target of rapamycin (mTOR) was significantly lower in the late CL than in the mid CL. Lysosome activation and expression of cathepsin-related genes (CTSB, CTSD, and CTSZ) showed significant increases in the late CL and were associated with an increase in cathepsin B protein. In addition, mRNA expression and activity of caspase 3 (CASP3), an apoptotic enzyme, were significantly higher in the late CL than in the mid CL. These results suggest simultaneous upregulation of autophagy-related factors, lysosomal enzymes and apoptotic mediators, which are involved in regression of the bovine CL.